A SCIENTIFIC ANALYSIS OF KANYAKUMARI (KUMARI KANDAM) (International Journal of Food and Nutritional Sciences, 2022)
Cape Comorin, also called Kaniyakumari, rocky headland on the Indian Ocean in Tamil Nadu state, south-eastern India, forming the southernmost point of the subcontinent. It is the southern tip of the Cardamom Hills, an extension of the Western Ghats range along the west coast of India.